Product And Tooling Design Of Slanted Glass Injection Mould For Visualization Of Flow Molten Plastic - Md Ali, Mohd Amran; M., Faizal; Kasim, Mohd Shahir; Raja Abdullah, Raja Izamshah; Subramonian, Sivarao (Penerbit UTM Press, 2015)
A two-plate plastic injection mould having a new method of embedded slanted glass at mould cavity side is designed where it can be used to visualize the flow of molten plastic material moving inside the mould cavity. Due to observation of molten plastic materials cannot be done in actual mould made from metal, therefore slanted glass mould is developed. This project shows the design process of slanted glass mould from initial plastic product design until mould tooling design. The plastic product and the slanted glass mould were designed using SolidWorks software. In designing and producing the injection molded plastic product, various factors are needed to be considering such as corner radius, draft angle and the product wall thickness Two different geometrical shapes of plastic products have been designed that were the flat and ring plastic product. Meanwhile for mould tooling design, the method to capture the flow pattern of molten plastic materials is the most considering factor in this project. Others considering factors included are location of feeding system, tolerance fitting and water cooling system. Thus, this project helps mould designer the important of design process should be considered during plastic design and tooling design especially for slanted glass injection mould.